2017
DOI: 10.1038/icb.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting A2 adenosine receptors in cancer

Abstract: Tumor cells use various ways to evade anti-tumor immune responses. Adenosine, a potent immunosuppressive metabolite, is often found elevated in the extracellular tumor microenvironment. Therefore, targeting adenosine-generating enzymes (CD39 and CD73) or adenosine receptors has emerged as a novel means to stimulate anti-tumor immunity. In particular, the A2 (A2a and A2b) adenosine receptors exhibit similar immunosuppressive and pro-angiogenic functions, yet have distinct biological roles in cancer. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 94 publications
0
57
0
3
Order By: Relevance
“…8 Accumulating evidences have revealed that A2A receptors respond to the adenosine stimulation and thus modulate multiple physiological and pathophysiological processes including memory formation, emotionstate alteration, inflammatory reaction, immune regulation, braininjury repair, and aging process. 9,10 Recent researches have revealed that elevated adenosine levels in extracellular tumor Abbreviations: BBB, blood-brain barrier; LDH, lactate dehydrogenase; SDF-1, Stromal cell-derived factor-1. microenvironment and the activation of A2A receptors contribute to the immune escape and promote the progression and metastasis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…8 Accumulating evidences have revealed that A2A receptors respond to the adenosine stimulation and thus modulate multiple physiological and pathophysiological processes including memory formation, emotionstate alteration, inflammatory reaction, immune regulation, braininjury repair, and aging process. 9,10 Recent researches have revealed that elevated adenosine levels in extracellular tumor Abbreviations: BBB, blood-brain barrier; LDH, lactate dehydrogenase; SDF-1, Stromal cell-derived factor-1. microenvironment and the activation of A2A receptors contribute to the immune escape and promote the progression and metastasis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The ecto-5 0 -nucleotidase CD73 causes accumulation of extracellular adenosine in the tumor microenvironment (TME), thereby promoting tumor immune escape, metastasis, and resistance to immune checkpoint inhibitors (1). Extracellular adenosine mediates its immunosuppressive activity essentially by activating the high-affinity A2A and low-affinity A2B receptors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, high quantities of adenosine are released into the extracellular space. Then this small molecule activates A2a receptors on effector T cells and increases intracellular cAMP to inhibit TCR-mediated signaling by preventing zeta-chain-associated protein kinase 70 (ZAP70) phosphorylation and activator protein-1 activation ( 36 ). The subsequently decreased TCR signaling leads to impaired CD25 expression and IL-2 production which are detrimental to effector T cells proliferation and activation.…”
Section: Soluble Mediators Derived From Tregmentioning
confidence: 99%